Incidence, Predictors and Outcomes of Major Bleeding in Patients Following Percutaneous Coronary Interventions in Australia - Wlodarczyk, J.; Ajani, A.; Kemp, D.; Andrianopoulos, N.; Brennan, A.; Duffy, S.; Clark, D.; Reid, Christopher (Elsevier Ltd, 2015)
Background: Major bleeding is a serious complication of percutaneous coronary intervention (PCI). We set out to investigate the incidence of major bleeding and its impact on hospitalisation and long-term mortality. Method: We examined seven years of registry data encompassing 16,860 PCI procedures. Results: Between 2005 and 2011 major bleeding increased from 1.3% to 3.4%. In patients with ST elevated myocardial infarction (STEMI), the rate increased from 2.3% to 6.4%. The increase remained significant after adjusting for patient and procedural characteristics (OR=1.09/year, p=0.001). Bleeding risk was highest in patients presenting with out-of-hospital cardiac arrest and cardiogenic shock (CS). Women, STEMI patients, those aged over 70yrs or weighing <60 kg were at higher risk. Glycoprotein IIb/IIIa-inhibitor use more than doubled the risk of bleeding (OR=2.28, p=<0.001). Mortality rates at one year were 4.18% overall and 7.9% in STEMI. Bleeding was a strong predictor of mortality after adjusting for potential confounders (HR=2.92, 95% CI: 2.08, 4.09). Bleeding significantly increased length of stay (med four days vs seven days) and rehospitalisation at 12 months (OR=1.36, 95% CI: 1.08, 1.70). Conclusions: Major bleeding rates post-PCI appear to be increasing in Australia. Bleeding increases hospitalisation and is associated with poor clinical outcomes.